TITIK TEMU KONSEP PENDIDIKAN KI HADJAR DEWANTARA DENGAN KURIKULUM MERDEKA BELAJAR (STUDI KOMPARATIF) - Angga Febriyatko; Khusnul Fatimah; Igajadwar Batalemba; Cut Dian Rahmawati (BASA Journal of Language & Literature, 2023)
The Free Learning Curriculum Policy is a learning program with the concept of independent education. This is in line with the thinking of the pioneer of our nation's education, namely Ki Hadjar Dewantara who directed education as an effort to liberate humans, both outwardly and mentally. The concept of independence can be seen in the freedom of educators to control learning and the freedom of students to take advantage of opportunities in learning widely and flexibly. This study aims to analyze the concept of Ki Hadjar Dewantara education with the Merdeka Belajar Curriculum that has been implemented today in Indonesia. The method in this research is a qualitative descriptive method with a literature study approach. Data in the form of information from several libraries. Data collection techniques by studying documents in books, journals, and others related to the educational concept of Ki Hadjar Dewantara and the Merdeka Learning Curriculum. The analysis technique used is data analysis using the Miles and Huberman interactive model. The findings of this study are that there is a relevant meeting point between the educational concept of Ki Hadjar Dewantara and the Independent Learning Curriculum in learning systems and methods, the position of students and educational techniques applied to create an independent education and Pancasila Student Profile character.